Evaluating the cytotoxic effects of the water extracts of four anticancer herbs against human malignant melanoma cells - Ling BB; Michel D; Sakharkar MK; Yang J (Dove Medical Press, 2016)
Binbing Ling,1,2 Deborah Michel,1 Meena Kishore Sakharkar,1 Jian Yang1 1Drug Discovery and Development Research Group, College of Pharmacy and Nutrition, University of Saskatchewan, Saskatoon, SK, 2Department of Biomedical and Molecular Sciences, Queen’s University, Cancer Biology & Genetics Division, Queen’s Cancer Research Institute, Kingston, ON, Canada Abstract: Malignant melanoma (MM) is the most dangerous type of skin cancer, killing more than 1,100 people each year in Canada. Prognosis for late stage and recurrent MM is extremely poor due to insensitivity to chemotherapy drugs, and thus many patients seek complementary and alternative medicines. In this study, we examined four commonly used anticancer herbs in traditional Chinese medicine, Hedyotis diffusa, Scutellaria barbata, Lobelia chinensis, and Solanum nigrum, for their in vitro antitumor effects toward human MM cell line A-375. The crude water extract of S. nigrum (1 g of dry herb in 100 mL water) and its 2-fold dilution caused 52.8%±13.0% and 17.3%±2.7% cytotoxicity in A-375 cells, respectively (P<0.01). The crude water extract of H. diffusa caused 11.1%±12.4% cytotoxicity in A-375 cells with no statistical significance (P>0.05). Higher concentrated formulation might be needed for H. diffusa to exert its cytotoxic effect against A-375 cells. No cytotoxicity was observed in A-375 cells treated with crude water extract of S. barbata and L. chinensis. Further high performance liquid chromatography-tandem mass spectroscopy analysis of the herbal extracts implicated that S. nigrum and H. diffusa might have adopted the same bioactive components for their cytotoxic effects in spite of belonging to two different plant families. We also showed that the crude water extract of S. nigrum reduced intracellular reactive oxygen species generation in A-375 cells, which may lead to a cytostatic effect. Furthermore, synergistic effect was achieved when crude water extract of S. nigrum was coadministered with temozolomide, a chemotherapy drug for skin cancer. Keywords: herbal extract, malignant melanoma, cytotoxicity, HPLC-MS/MS, reactive oxygen species